Homogeneity versus heterogeneity of cultural values: An item-response theoretical approach applying Hofstede's cultural dimensions in a single nation - Mazanec, J.; Crotts, J.; Gursoy, D; Lu, L. (Pergamon, 2015)
The focus of this study is threefold. First it tested the validity and reliability of a scale designed to measure Hofstede's five cultural dimensions at the individual or psychological level across two large (n>500) convenience samples of the United States population. Once deemed an appropriate measure, the scale was applied to questions testing the homogeneity of the measures. The questions refer to the speed to which acculturation occurs within an immigrant population and the degree to which purported regional geographic differences constitute distinct cultural values as measured by Hofstede. Implications for tourism marketers as well as a call for future research are discussed.